Virtual assistants and the quality of service to the customer - Trujillo Valdiviezo, Guido; Mejía Ayala, Desmond; Rodríguez Alegre, Lino (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
In an environment characterized by relentless technological development, ICTs have disrupted the way people communicate and interact. Virtual assistants, by automating customer service processes, minimize the intervention of people, reducing resources of business entities. Likewise, they manage to strengthen their position in the market by adding value to their portfolio, and in this way, they manage to increase the relationship with customers. It is concluded that virtual assistants positively influence customer service, since it was possible to improve indicators such as empathy, reliability in service and responsiveness.